Outcome of Inferonasal Conjunctival Autograft in Pterygium Surgery - Adhikari, Pragati Gautam; Joshi, Sagun Narayan (Nepal Medical College Journal, 2021)
This study was done to evaluate the outcome of pterygium excision with inferonasal conjunctival autograft at a tertiary eye care centre. Retrospective analysis of medical records of primary pterygia patients operated by a single surgeon between 2017 to 2020 were analyzed. A total of 43 patients who met the inclusion criteria were included in the study. The demographic variables, along with size of pterygium and recurrence over a period of six month follow up was noted. The mean age of patients was 46.97 years (29-74 years). The mean size of pterygium was 3.17 mm. Recurrence was seen in 3 eyes over a period of 6 months. Graft edema was observed in 11 patients and graft hemorrhage along with congestion was seen in 8 cases which resolved over a 3 weeks follow up period. Mild conjunctival scarring was seen over donor area in 5 of the eyes. Pterygium excision with inferior conjunctival autograft is an effective alternative technique to superotemporal autograft technique.